Patai's Chemistry of Functional Groups 2009
DOI: 10.1002/9780470682531.pat0130
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Compounds Containing CC Double Bonds

Abstract: Introduction Excited States Z – E Isomerizations [2 + 2] Photodimerizations [2 + 2] Photocycloadditions of Alkenes to Enones DI ‐π‐Methane Rearrangement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 171 publications
0
1
0
Order By: Relevance
“…Just as with furfural, malonic acid is a bioadvantaged chemical, meaning petrochemical processes cannot compete with biochemical production. The subsequent decarboxylation of the Knoevenagel adduct in the same pot gave 2-furanacrylic acid ( 2 ) in 87% isolated yield. , Our previous study showed that 2 can be dimerized directly through photocycloaddition in the solid state to give CBDA-2 (head-to-head dimer), and all other related reports have also suggested that the β-form crystal (head-to-head packing) is the preferred packing conformation of 2 . ,, As such, despite its great potential applications in materials, the cyclobutane-1,3-diacid (head-to-tail dimer of 2 , CBDA-5, shown in Scheme ) has never been reported before, as it would need to arise from the α-form crystal (head-to-tail packing) of 2 . It seems that the intermolecular hydrogen bonds in the solid state disrupt the weak complementary π–π stacking between adjacent acid molecules that could lead to the formation of the α-form crystal., Thus, we hypothesized that ethyl 2-furancarylate might offer the desired α-form packing in the solid state because the strong intermolecular hydrogen bonds between the carboxylic acid groups are removed. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…Just as with furfural, malonic acid is a bioadvantaged chemical, meaning petrochemical processes cannot compete with biochemical production. The subsequent decarboxylation of the Knoevenagel adduct in the same pot gave 2-furanacrylic acid ( 2 ) in 87% isolated yield. , Our previous study showed that 2 can be dimerized directly through photocycloaddition in the solid state to give CBDA-2 (head-to-head dimer), and all other related reports have also suggested that the β-form crystal (head-to-head packing) is the preferred packing conformation of 2 . ,, As such, despite its great potential applications in materials, the cyclobutane-1,3-diacid (head-to-tail dimer of 2 , CBDA-5, shown in Scheme ) has never been reported before, as it would need to arise from the α-form crystal (head-to-tail packing) of 2 . It seems that the intermolecular hydrogen bonds in the solid state disrupt the weak complementary π–π stacking between adjacent acid molecules that could lead to the formation of the α-form crystal., Thus, we hypothesized that ethyl 2-furancarylate might offer the desired α-form packing in the solid state because the strong intermolecular hydrogen bonds between the carboxylic acid groups are removed. ,,, …”
Section: Resultsmentioning
confidence: 99%